Tether‐Directed Regioselective Synthesis of an Equatorialface Bisadduct of Azafullerene Using Cyclo‐[2]‐octylmalonate. Issue 22 (26th March 2019) - Stergiou, Anastasios; Asad, Karam; Kourtellaris, Andreas; Chronakis, Nikos; Tagmatarchis, Nikos
Abstract: Bisazafullerene (C59 N)2 has been functionalized under aerobic conditions with cyclo ‐[2]‐octylmalonate through a Mannich‐type reaction, furnishing the corresponding monoadduct. A regioselective tether‐directed Bingel cyclopropanation reaction was then carried out on the azafullerene core to yield a single bisadduct. Spectroscopic analysis of the formed bisadduct showed it to have a C 1 symmetrical structure, making it inherently chiral. Single‐crystal X‐ray analysis revealed the addition pattern of the azafullerene bisadduct to be equatorialface . Examination of the optical properties showed the evolution of new absorption bands, which can be used as signatures for the characterization of equatorialface bisadducts of C59 N. Finally, redox assays showed that the LUMO level of the equatorialface bisadduct was increased compared to that of the parent (C59 N)2 . Abstract : Towards regioselective C59 N functionalization : The tether‐directed regioselective synthesis of an inherently chiral equatorialface bisadduct of azafullerene is presented (see figure).